The Influence of Service Quality, Image and Trust on Customer Satisfaction on Primary Police Cooperation (Primkopol) Mitra Maju Jaya Polda Metro Jaya - Palti Raja Sinaga, Palti Raja Sinaga; Ani Nuraini, Ani Nuraini; Nurminingsih, Nurminingsih; Mariati Tamba, Mariati Tamba (Journal of Entrepreneur and Business, 2023)
This study aims to determine (1) the effect of service quality on customer satisfaction, (2) the effect of image on customer satisfaction, (3) the effect of customer trust on customer satisfaction, (4) the effect of service quality, image and trust on customer satisfaction. The population of this research is all members of the Mitra Maju Jaya cooperative. By using a random sampling technique, the minimum sample size is determined by 100 people, which is calculated using the Slovin formula. Research data were collected by distributing questionnaires to respondents, then processed with the help of the SPSS program. The results of this study indicate that (1) service quality has a positive and significant effect on cooperative customer satisfaction, (2) image has a negative and significant effect on cooperative customer satisfaction, (3) trust has a positive and significant effect on cooperative customer satisfaction, (4) service quality , image and trust have a significant effect on cooperative customer satisfaction. Keywords: Service Quality, Image, Trust, Satisfaction, Cooperativ